Service Recovery, Justice and Customer Satisfaction: Evidence from Internet Service Users in Nepal - Adhikari, Shiva Raj; Shrestha, Hira Lal; Neupane, Dasarath; Ghimire, Ashim (International Journal of Atharva, 2026)
Background: In Nepal’s highly competitive internet service market, service failures are inevitable. Effective service recovery has become a critical determinant of customer satisfaction and loyalty, yet empirical evidence on this dynamic within the country’s Internet Service Provider (ISP) sector remains limited.Objectives: This study aims to evaluate the influence of key service recovery dimensions—timeliness, employee behavior, fairness in pricing, and follow-up—on customer satisfaction among WorldLink internet users in the Kathmandu Valley.Methods: A quantitative, cross-sectional research design was employed. Data were collected from 442 WorldLink users in Kathmandu Valley using a structured online questionnaire. The proposed model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM), grounded in justice theory.Findings: The results demonstrate that all four service recovery dimensions have a significant positive influence on customer satisfaction. Timeliness (β = 0.329) and fairness in pricing (β = 0.299) emerged as the strongest predictors, followed by employee behavior (β = 0.245) and follow-up (β = 0.118). The model explained 75.4% of the variance in customer satisfaction, underscoring its strong explanatory power.Conclusion: The study concludes that a holistic service recovery strategy, integrating procedural, interactional, and distributive justice, is essential for enhancing customer satisfaction in Nepal’s ISP sector. While WorldLink excels in timeliness and employee behavior, strengthening follow-up mechanisms is a key area for improvement.Novelty: This research is among the first to empirically validate the applicability of justice theory to service recovery in Nepal’s ISP sector, offering a comprehensive analysis of multiple recovery dimensions using robust PLS-SEM techniques within a unique emerging market context.